Discussion on Research Approaches of Traditional Chinese Medicine Syndromes of Postmenopausal Osteoporosis - Yuqing SUN; Bingqi WANG; Xiang CHEN; Xuefeng ZHENG; Yanping LIN (康复学报)
This authors analyze the interrelationship between syndrome types of traditional Chinese medicine (TCM) and Western medicine (WM) indicators based on the nosogenesis of postmenopausal osteoporosis (PO), propose the thinking about new direction of diagnosis and treatment of postmenopausal osteoporosis from integrated medical perspectives.